Employee Payroll Information System at Manunggal Village Head Office - Susyla, Esti Fitri; Manalu, Mamed Rofendi (Pascal: Journal of Computer Science and Informatics, 2023)
The existence of the Employee Payroll Information System at the Manunggal Village Office provides convenience to its users. The procedure used is simpler so that the Payroll Information System at the Manunggal Village Head Office is more efficient and effective. Therefore, the author designed a Payroll Information System at the Manunggal Village Head Office using Microsoft Visual Basic 2010 software and MY SQL as the database. This research is a research and development research with development and implementation methods. Data obtained through literature study and interviews. The system development method used is an output, process and data oriented methodology. The design of information systems is a context diagram, and data flow diagrams. By implementing the Payroll Information System at the Manunggal Village Head Office, it can make it easier when reporting and in making reports that are processed quickly and well. The application of the Payroll Information System at the Manunggal Village Head Office using Visual Basic 2010 can help performance in the Manunggal Village Head Office.